'Direct democracy now!': The Greek indignados and the present cycle of struggles. (July 2013) - Sotirakopoulos, Nikos; Sotiropoulos, George
This article's ambition is to critically analyse the resistance of the Greek people to the country's custody under the Troika that has led to a severe financial and social crisis. Emphasis is given to the 'Outraged' of Syntagma Square and their daily protests during the summer of 2011; a movement that has remained underreported in relation to other similar phenomena, despite the huge number of participants, and the intensity of its clash with the state. In addition, besides the empirical investigation of the Greek case, the article argues that it is of particular importance to note the movement's cultural resources, as well as the inner class and ideological divisions. Also, the study attempts to fit the case of Greece within the global capitalist crisis and the struggles that have arisen as a response.